GE_GERICHTE A/1637/2025 vom 26. August 2025 - GE Cour de justice (2025)
OBJET DU LITIGE;OPPOSITION(PROCÉDURE);CONDITION DE RECEVABILITÉ;PROMOTION;ÉGALITÉ ENTRE HOMME ET FEMME;NULLITÉ;ANNULABILITÉ;EMPLOI(TRAVAIL);CONFLIT D'INTÉRÊTS | LU.13; LU.43; RPers.98; RPers.99; RPers.102; LEg.3; LEg.5; LEg.6; LEg.10; LEg.13; LPA.2.letd